Correlating magnetic resonance imaging characteristics with motor outcome in cerebral palsy children with white matter injury - Narkhede, Nilima Ananda; Save, Sushma (Nepal Journal of Neuroscience, 2023)
Introduction: Cerebral palsy (CP) is the term used to describe individuals with a movement disorder resulting from non-progressive disturbance to the developing brain. The diagnosis of CP is based on the presence of a motor deficit, and they manifest with reduced motor capacity. The most widely utilized classification system for the severity of motor limitations is the gross motor function classification system (GMFCS). Material and Methods: We tried to describe the white matter injury on Magnetic Resonance Imaging (MRI) in children with cerebral palsy irrespective of clinical subtype. We also studied if there was association between white matter injury on MRI in children with cerebral palsy and motor outcomes-gross motor function classification system Expanded and Revised(GMFCS E &R). It was an observational, Cross sectional Descriptive study with analytical wing aged between 6 months to 12 years of age carried out for 8 months. Children diagnosed to have cerebral palsy on history and clinical examination were enrolled in the study. Results: A total of 50 children diagnosed with cerebral palsy were enrolled in our study. Majority of the study sample were <5years old (29) and males (31). We found that symmetrical involvement, severe white matter loss in the hemisphere and callosal thinning were the strongest predictors of poor gross motor function. Bilateral, extensive WM (white matter) loss was more likely to result in quadriplegia, whereas volume loss in the posterior-mid WM more frequently resulted in diplegia. Asymmetrical involvement was associated with less extensive hemispheric involvement than symmetrical WMI (White matter injury). Cysts, deep grey abnormality, and Wallerian change in the PLIC (Posterior limb of Internal Capsule) and cerebral peduncles were all more commonly seen in association with unilateral and asymmetric patterns of WMI. All children with unilateral WMI functioned at GMFCS levels I or II or III whereas bilateral involvement was associated with wheeled mobility (GMFCS levels IV–V). Motor outcomes for children with asymmetrical WMI fell between those with symmetrical and unilateral WMI on MRI. Conclusion: Laterality/ symmetry of WMI along with extent and location of WM loss can predict gross motor function in Cerebral palsy.